The effect of organizing supervision on public perception through public trust in the 2024 simultaneous elections in Ngawi Regency - Anita Setia Mega Putri; Syamsul Wathoni (Journal of Community Development and Disaster Management, 2026)
This study analyzes the effect of organizing supervision on public perception through public trust in the 2024 simultaneous elections in Ngawi Regency. Supervisory organization is understood as an institutional management process that includes planning, organizational structure, coordination, and evaluation, which plays a role in shaping the legitimacy of supervisory institutions and public assessments of electoral integrity. The study used a quantitative approach with a survey method to 400 respondents who were randomly selected based on the Permanent Voters List of Ngawi Regency. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the direct and indirect influence, as well as the role of public trust as a mediator. The results showed that the organization of supervision has a positive and significant effect on public perception (③=0.228; p < 0.05) and public trust (③=0.158; p < 0.05), while public trust also has a significant effect on public perception (③=0.428; p < 0.05). In addition, public trust has been shown to partially mediate the relationship between surveillance organization and public perception (⑧indirect = 0.068; p < 0.05). This finding confirms that the effectiveness of election surveillance is determined not only by procedural compliance, but also by the ability of supervisory agencies to build public trust through transparent, accountable, and communicative practices. This study provides practical implications for strengthening election supervision and strategies to increase the positive perception of the community at the local level.